Adherence to preventive measures versus incidence of ventilator-associated pneumonia - Silva Lourençone, Emerson Matheus (2019)
Background and Objectives: Ventilation-Associated Pneumonia (VAP) is the infection related to health care that most affects patients in mechanical ventilation admitted to the Intensive Care Unit (ICU), and prevention measures are necessary to ensure safe care. The objective of this study was to evaluate the adherence rate of the preventive actions of the nursing team for Ventilation-Associated Pneumonia after restructuring and application of the prevention protocol and to verify the incidence density rates of patients with VAP. Methods: Observational, longitudinal study of bundle adherence analysis after its restructuring, performed in a general adult ICU between May and November 2017. Sample for convenience with 154 patients on mechanical ventilation. Evaluated nursing care: oral hygiene with chlorhexidine 0.12%; high headboard; cuff pressure; and position of the filter. The intervention was continuous reinforcement of the team to carry out the preventive measures. Infection Control Service calculated monthly VAP rates for comparison. Results: The average adherence rate of preventive measures in 1,296 evaluations showed adequacy in: 94% filter position; 88.7% high bed; 77.3% oral hygiene with chlorhexidine 0.12%; and 91.7% cuff pressure control. Conclusion: With continuous monitoring and reinforcement, the preventive measures for VAP, performed by the nursing team, remained above 77%, with a concomitant decrease in the rate of VAP. Keywords: Ventilation-associated pneumonia. Cross infection. Intensive care units. Critical care.